2015
DOI: 10.1186/s12943-015-0295-3
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 signaling regulates the epithelial–mesenchymal transition and invasion of breast cancer in a Slug-dependent manner

Abstract: BackgroundThe epithelial–mesenchymal transition (EMT) is crucial for the invasion and metastasis of breast cancer. However, how Notch signaling regulates the EMT process and invasion in breast cancer remains largely unknown.MethodsThe impact of Notch1 silencing by specific shRNAs on the EMT and invasion of human breast cancer MCF-7 and MDA-MB-231 cells as well as xenografts was tested by western blot, real-time polymerase chain reaction (RT-PCR), immunofluorescence, transwell, and immunohistochemistry assays. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
155
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(167 citation statements)
references
References 43 publications
10
155
0
2
Order By: Relevance
“…It has been demonstrated that the metastatic role of Notch‐1 which activates EMT by up‐regulating mesenchymal markers including β‐catenin, snail, slug, vimentin, etc. as well as by down‐regulating epithelial markers, that is E −cadherin in BCa . Our results are consistent with these findings.…”
Section: Discussionsupporting
confidence: 92%
“…It has been demonstrated that the metastatic role of Notch‐1 which activates EMT by up‐regulating mesenchymal markers including β‐catenin, snail, slug, vimentin, etc. as well as by down‐regulating epithelial markers, that is E −cadherin in BCa . Our results are consistent with these findings.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, intraperitoneal administration of ATRA at dosages reducing the primary tumor mass causes a significant down-regulation of the NOTCH1, SNAIL, and SLUG mRNAs. 3 These in vivo data are in line with the down-regulation of NOTCH1 and SNAIL observed in SKBR3 cells and the recently reported role of SLUG as a mediator of the EMT and metastatic processes activated by NOTCH1 in xenografts of retinoid-insensitive MDAMB231 cells (61). The antimetastatic properties of ATRA can be exploited at the clinical level for the design of retinoid-based therapeutic strategies aimed at the treatment or chemoprevention of breast cancer.…”
Section: Discussionsupporting
confidence: 68%
“…High Notch1 levels have been linked to poor prognosis in breast cancer [5], where Notch1 has been shown to induce epithelial-to-mesenchymal transition (EMT) [6, 7], upregulate extracellular matrix metalloproteinases [8], and induce a switch to glycolytic metabolism [9], contributing to both tumor initiation and progression. Similarly in prostate cancer, Notch1 supports cancer cell survival and EMT [10].…”
Section: Introductionmentioning
confidence: 99%